Konsentrasi Ekspor Provinsi Jawa Tengah - Rejekiningsih, Tri Wahyu (Jurnal Ekonomi Kuantitatif Terapan, 2012)
The research objective was to identify the export focus of Central Java Province, in commodities side and market side. The data which used are secondary data which had been published by BPS and other source which have linkage. The research objects was the amount and export value of Central Java Province, which consists of some kinds of commodities and the destination countries, on 2001-2009. The analysis revealed that there are five dominant comodities of Central Java province export, they are: threads and textile industry; other industries; BBM; wood industry; cork and straw; and cattle breeding. The threads and textile industry comodity was become the export concentration. Other that, also revealed that there are five export destination countries, they are : USA; Japan; Singapore; Germany; and Republic of Korea, and the USA become the market concentration of Central Java province exports. Based on the identification, threads and textile industry consist of 52 goods, and has large either amount or export value. So if compared with other export comodities, then threads and textile industry comodity dominant the Central Java province’s exports. While USA’s market dominants export destination of Central Java province, because based on the data from BPS known that export to USA includes 6 (six) comodities, which are: threads and textile industry; machine industry, electricity and electronic; fur and fur industry; wood industry; cork and straw; cattle breeding; and other industries.
Keywords: export concentration; market export concentration; comparative advantage; competitive advantage